Needs Analysis for E-WLOAD - Ariffin, Asma Hanee; Abdul Wahid, Rohaizah; Mansor, Marzita; Sulaiman, Suliana (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Isu beban tugas berlebihan di kalangan pendidik telah menghasilkan penciptaan e-WLOAD, sistem pengagihan beban tugas pensyarah (pengajaran dan pengurusan) bagi mengatasi masalah ketidak-seimbangan beban tugas dan kepakaran dalam organisasi. Walaupun terdapat pelbagai sistem dan aplikasi bagi proses pengagihan tugas di pasaran, namun ianya tidak mengkhususkan kepada bidang pendidikan yang melibatkan pelbagai sumber pengetahuan dan proses yang kompleks. Pembentangan ini memfokuskan kepada kejuruteraan keperluan bagi penghasilan keperluan fungsian sistem. Proses yang terlibat adalah elisitasi dan analisis keperluan menggunakan teknik penilaian dokumen dan temubual, membina spesifikasi keperluan dan validasi spesifikasi. Dapatan akhir proses berupaya menggariskan secara terperinci keperluan fungsian sistem dari perspektif proses dan data yang terlibat. Sistem e-WLOAD mampu mencadangkan pensyarah yang bersesuaian bagi kursus berdasarkan kriteria bidang kepakaran dan kelayakan, skor kekerapan dan beban kredit pengajaran seterusnya mampu menjana jadual beban tugas pengajaran jabatan yang menitik beratkan keseimbangan beban kredit antara pensyarah dan sela masa semester pengajaran. Sistem juga mampu mencadangkan pensyarah bagi tugas pengurusan sesuai dengan kelayakan, kepakaran dan beban semasa. Needs Analysis for E-WLOAD Abstract: The issue of excessive workload among educators has resulted in the creation of e-WLOAD, a lecturer's workload distribution system (teaching and management) to overcome the problem of workload imbalance and expertise in the organization. Although there are various systems and applications for the task distribution process in the market, but it does not specialize in the field of education which involves various sources of knowledge and complex processes. This presentation focuses on engineering requirements for the production of system functional requirements. The process involved is elicitation and needs analysis using document evaluation and interview techniques, constructing specification requirements and validation of specifications. The final findings of the process are able to outline in detail the functional requirements of the system from the perspective of the process and the data involved. The e-WLOAD system is able to recommend suitable lecturers for the course based on criteria of expertise and qualifications, frequency scores and teaching credit load which in turn is able to generate a departmental teaching workload schedule that emphasizes the balance of credit load between lecturers and teaching semester intervals. The system is also able to recommend lecturers for management tasks in accordance with current qualifications, expertise and load. Keywords: e-WLOAD, Needs Analysis, Workload.